1995
DOI: 10.1152/ajpgi.1995.268.2.g374
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli adherence to intestinal epithelial monolayers diminishes barrier function

Abstract: The mechanism by which enteropathogenic Escherichia coli (EPEC) causes diarrhea remains elusive. Several alterations within the host cell have been demonstrated to occur following EPEC attachment including increases in intracellular Ca2+ concentration and rearrangement and phosphorylation of several cytoskeletal proteins. The consequences of these intracellular perturbations on host cell function, however, have not been determined. The aim of this study was to examine the effect of EPEC adherence on intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 0 publications
6
148
0
Order By: Relevance
“…We have shown previously that EPEC alters the tight junction barrier function of the host intestinal epithelial tissues (Spitz et al, 1995). Additional studies from our laboratory have demonstrated that one mechanism by which EPEC enhances paracellular permeability is by phosphorylating MLC 20 (Yuhan et al, 1997).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…We have shown previously that EPEC alters the tight junction barrier function of the host intestinal epithelial tissues (Spitz et al, 1995). Additional studies from our laboratory have demonstrated that one mechanism by which EPEC enhances paracellular permeability is by phosphorylating MLC 20 (Yuhan et al, 1997).…”
Section: Introductionmentioning
confidence: 81%
“…We are far from understanding the regulation of each of these molecules and the interactions that very likely exist between them. It is becoming increasingly clear that tight junctions are altered by both physiological (Madara and Pappenheimer, 1987;Turner et al, 1997) and pathophysiological processes (Spitz et al, 1995;Yuhan et al, 1997;Philpott et al, 1998;Sonoda et al, 1999). Here, we examine the impact of an important and interesting enteric bacterial pathogen, enteropathogenic Escherichia coli, on the tight junction-associated, transmembrane protein occludin.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Enteropathogenic E. coli (EPEC), a diarrhoeagenic pathogen of importance in developing countries (Nataro and Kaper, 1998), has been shown to alter the tight junction barrier function of the host intestinal epithelial tissues (Spitz et al ., 1995). Intimate attachment of EPEC to host intestinal epithelial cells is the result of interaction between a bacterial outer membrane protein intimin and the translocated intimin receptor (Tir) that is injected into the host cell by a type III secretion system Deibel et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%